Analisis Penurunan Lapisan Tanah di Bawah Struktur Breakwater Timur Laut Pelabuhan Patimban - Dwisa, Cokorda Bagus Purnama; Khomeiny, Ali Sumara El; Bimarso, Wahyono; Farhan Abdilah, Muhammad (Jurnal Teknik Transportasi, 2024)
Breakwater is a coastal building structure built to protect facilities in coastal areas. To protect from challenging climatic conditions, this building plays an important role to protect the port from waves and reduce wave energy that will hit the port so that the waves that come and hit the port have broken and will not interfere with shipping activities in the port water area. After the breakwater building at Patimban port was completed in 2021, there is a problem, settlement of breakwater as high as ± 2.7 m which is known from the results of monitoring during the maintenance period for 730 days or for 2 years after the breakwater construction period. In order for the settlement to be overcome, it is necessary to analyze the immediate settlement, settlement in primary consolidation, settlement in secondary consolidation, degree of consolidation of the soil layer under the breakwater structure appropriately so that the value of the settlement can be known and can choose improvements for the decrease in breakwater elevation with existing conditions at Patimban port.